Incorporating Black women's perspectives into long-acting reversible contraception implementation - William C. Livingood, Ph.D; Katryne Lukens Bull, M.P.H; Staci Biegner, M.D; Andrew M. Kaunitz, M.D; LaRonda Howard, M.P.H; Vanessa Jefferson; Pia Julia Geisselmaier, M.P.H; Isabelle Michel, M.P.H; Lori Bilello, Ph.D (Elsevier, 2022)
Objective: To study urban, predominantly Black women's expressed opinions and beliefs related to the use of contraceptives to better inform implementation strategies designed to increase the use of highly effective contraceptives among minoritized and low-income women. Design: Focus group interviews with women, in conjunction with a community-based organization providing programs for underserved women with a mission of improved women and infant health. Setting: Focus groups were conducted, and women were recruited from clinical sites in predominantly African American urban neighborhoods in a southeastern US city. Patient(s): Self-identified 18-35-year-old women recruited from clinical sites in the urban core of the city with an 80% African American population. Intervention(s): No interventions tested. Main Outcome Measure(s): Black women's opinions and concerns about contraception. Results: Key insights from the focus group results for healthcare providers include the following: the importance of framing discussions with patients within the context of the patients' goals; need to acknowledge and respect the support systems that women rely on for child birthing and childcare; recognition of the clinician's role as a trusted and respected source of information; and need to understand and be prepared to address much of the inaccurate and misleading information that can interfere with the patients' optimal choices for contraception. Conclusions: A critical component for applying the implementation science theory to increase the use of evidence-based practices, such as implementation of highly effective contraceptives, requires understanding women's perspectives of the factors influencing their decisions to use highly effective contraceptives. This study provides important insights into the following: the potential barriers inherent in minoritized women's concerns about contraceptives and how these insights can inform implementation strategies such as patient-centered counseling and education to overcome those barriers.